Ḥikāyat al-Sha‘bīyah al-Minangkabāwīyah Bundo Kanduang bayn al-Usṭūrah wa-al-Khurāfah: al-Manẓurah al-Dīnīyah - Zuriyati, Zuriyati (Studia Islamika, 2011)
This article discusses Bundo Kanduang folklore from a religious perspective. Folklore is a literary work that describes the life story of a figure or tells about the origin of a region which is intended to provide guidance for community. In some cases, it also becomes a medium to disseminate religious teachings or moral tenets. Despite these primary goals, folklore also aims to entertain the community through stories. This article ultimately attempts to understand the community's belief to Bundo Kanduang folklore from the Islamic orthodoxy point of view. Conservative Muslims tend to consider people's excessive belief to one figure or to treat him/her as a cult is a heresy (bid'ah) which contradicts Islamic teaching.DOI: 10.15408/sdi.v18i1.443